Application of Linear Programming for Profit Maximization: A Case of Paints Company, Pakistan - Izhar, Syed Usman (Asian Accounting and Auditing Advancement, 2016)
The purpose of the study is to highlight the effectiveness of linear programming in determining of optimal combination of various products that an organization produces to maximize contribution. For this purpose, data for the month of July 2013 of a paint company in Pakistan has been obtained for one of the main products “Plastic Emulsion, " produced in three different sizes (quarter, gallon, and drummy). The simplex method is used to determine the optimal mix of these sizes to be produced to maximize contribution. The results show that the company can earn maximum contribution by only investing its resources (raw material) in the production of gallons and producing 444 units of it thus generating a contribution of Rs. 162038. This study will recognize this company and also the other manufacturing companies, particularly in Pakistan, with the effectiveness of linear programming for making decisions about the optimal combination of products to be produced to obtain the maximum return.